Analisi Kepuasan Nasabah Pada PT. Bank Tabungan Negara (Persero) Tbk. Kantor Cabang Syariah Yogyakarta - Aidha Trisanthy (Jurnal Aplikasi Bisnis, 2016)
Complex competition in syariah' banking industries requires each player in that sector to sharp strata in order to win the rivalry, particularly on how to satisfy their customer. This study intends to investigate customer satisfaction in BIN syariah Yogyakarta using six elements specifically compliance, assurance, reliability, tangible, empathy and responsiveness. The result shows that the customers satisfy only on two dimensions explicitly compliance and dimension while in four other aspects (reliability, tangibles, empathy and responsiveness) they feel unsatify. It means that there is a negative gap between service quality that BTN given and their customers perception.